Comparison of Length of Stay of Severe and Critical COVID-19 Patients with Diabetes Mellitus, Hypertension, and Other Comorbidities - Sugiri, Yani Jane; Fatoni, Arie Zainul; Rosita, Theresia Daniella (Jurnal Respirologi Indonesia, 2025)
Background: Coronavirus Disease-19 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). In 2020, a disease known as COVID-19 became a global pandemic. This disease can spread through the air or mucosal contact with the body. The impact of COVID-19 varies greatly from person to person and depends on various factors, including any pre-existing health conditions. This study aimed to determine the hospitalization period for severe and critical COVID-19 patients with comorbidities such as diabetes mellitus, hypertension, obesity, heart failure, stroke, pregnancy, coronary artery disease, and asthma in the Intensive Care Unit at RSUD Dr. Saiful Anwar in Malang. Methods: This study used an observational analysis method by taking secondary data from medical records and out-of-hospital data of patients admitted to the Intensive Care Unit. The data that has been collected is carried out by a normality test using the Saphiro-Wilk test then the Kruskal-Wallis test and the Dunn test as a follow-up test. Results: The study was dominated by subjects less than 60 years of age, male, and most had comorbidities.  It was found that only in death outcome group has a significance value of P<0.05, with the longest hospital stays in patients without comorbidities and patients with diabetes mellitus only (ICU Median=7.5 days), while the shortest length of stay was obtained in patients with comorbidities other than diabetes and hypertension (ICU Median=3.5 days). Conclusion:  The presence of multiple comorbidities in patients is associated with greater severity of illness, resulting in longer hospital stays among those who are discharged. Conversely, patients who experience death outcomes tend to have shorter lengths of stay in the hospital.